Effect of acupuncture in patients with postprandial distress syndrome: study protocol for a randomized controlled trial - Yan, Zhaobo; Xu, Xuan; Liu, Mailan; MuRong, Zhimiao; Zhong, Huan; Luo, Rong; He, Haolong; Liu, Weiai; Du, Geshu; Liu, Mi (Frontiers in Medicine, 2025)
BackgroundPostprandial distress syndrome (PDS) is the prominent subtype in patients with functional dyspepsia (FD) and currently lacks a satisfactory treatment. Acupuncture has become a promising alternative and complementary therapy for managing FD. However, high-level clinical evidence supporting the use of acupuncture for FD is limited.MethodsThis study is a multicentre, double-dummy, single-blind, randomized, active-controlled trial. Two hundred and one eligible participants will be randomly assigned into three groups: a verum acupuncture plus placebo group, an itopride plus sham acupuncture group, and a sham acupuncture plus placebo group. This study consists of a 1-week screening period, a 4-week treatment period, and a 12-week follow-up period. During the intervention period, participants will receive 12 sessions of verum or sham acupuncture treatment (one session per day, three sessions per week, for 4 weeks) along with 50 mg itopride tablets or 50 mg itopride placebo tablets 3 times a day for 20 days (5 continual days a week for 4 weeks). The response rate (patients who had adequate relief of gastric symptoms will be considered positive responders) and the elimination rate of cardinal symptoms (postprandial fullness and early satiation) are the primary indicators to evaluate the overall acupuncture effect for PDS. Secondary outcome measures will include the Nepean Dyspepsia Symptom Index (NDSI), the short form-Nepean Dyspepsia Life Quality Index (SF-NDLQI), the Hospital Anxiety and Depression Scale (HADS), and related hormone concentrations. Participants’ expectations toward acupuncture treatment will also be assessed, and adverse events will be recorded for safety assessment. All analyses will adhere to an intention-to-treat principle.DiscussionIn conclusion, this trial will determine the efficacy and safety of acupuncture for PDS and provide more high-level evidence to support its application in treating FD.Trial registrationIdentifier [ITMCTR2024000510].